Training and work characteristics of mid-level nursing teachers - Vânia Marli Schubert Backes; Jouhanna do Carmo Menegaz; Bruna de Souza Francisco; Kenya Schmidt Reibnitz; Lauriana Medeiros Costa (Rev Rene)
This study aimed to identify teacher training and professional performance of teachers in mid-level nursing training schools. A quantitative study performed in 2012 through questionnaires with 41 teachers from eleven mid-level nursing training schools in the states of Rio Grande do Norte and Santa Catarina. General characteristics of the teacher, initial and continued education and work characteristics are presented. It is concluded that it is necessary to point out guidelines for the training/graduation of mid-level professionals and educators, and it is also necessary to globally value teachers, not only those acting in the federal network.